2007
DOI: 10.1529/biophysj.107.103911
|View full text |Cite
|
Sign up to set email alerts
|

Protein Free Energy Landscapes Remodeled by Ligand Binding

Abstract: Glucose/galactose binding protein (GGBP) functions in two different larger systems of proteins used by enteric bacteria for molecular recognition and signaling. Here we report on the thermodynamics of conformational equilibrium distributions of GGBP. Three fluorescence components appear at zero glucose concentration and systematically transition to three components at high glucose concentration. Fluorescence anisotropy correlations, fluorescent lifetimes, thermodynamics, computational structure minimization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…seems to be functionally relevant because it has been hypothesized to facilitate ribose transfer in the permease complex-a partially closed conformation with a more weakly bound ribose might help in providing an easier release of ribose into the membrane-bound permease (3). A similar twisted intermediate state was suggested for the D-Glucose binding protein, another member of the same family, based on experimental studies using disulfite-trapping and fluorescence spectroscopy (36,37). Very recently, accelerated molecular dynamics were used to suggest the existence of a semiclosed state for the Maltose binding protein, a member of a closely related family (38,39).…”
Section: Significancementioning
confidence: 75%
“…seems to be functionally relevant because it has been hypothesized to facilitate ribose transfer in the permease complex-a partially closed conformation with a more weakly bound ribose might help in providing an easier release of ribose into the membrane-bound permease (3). A similar twisted intermediate state was suggested for the D-Glucose binding protein, another member of the same family, based on experimental studies using disulfite-trapping and fluorescence spectroscopy (36,37). Very recently, accelerated molecular dynamics were used to suggest the existence of a semiclosed state for the Maltose binding protein, a member of a closely related family (38,39).…”
Section: Significancementioning
confidence: 75%
“…In enzyme kinetics, factor and/or ligand binding and differences in environmental conditions, such as temperature, pH, or ionic strength, affect enzyme function by altering the energy landscape, biasing the conformational coordinate to distinct conformational states and thus affecting the reaction coordinate and causing changes in turnover rates (45). An increasing number of studies have shown the effects of conformational sampling on ligand binding, catalysis, or product formation (46 -49).…”
Section: Discussionmentioning
confidence: 99%
“…The recent energy landscape picture of protein folding, [16][17][18][19] in which protein dynamics are depicted as diffusion on a high-dimensional potential energy surface, established the idea that proteins can visit a pre-existing ensemble of conformations, including the 'native' structure, even in the absence of the ligand. Conformational selection proposes that the ligand selects and stabilizes a high-affinity state out of this preexisting ensemble.…”
Section: A Historical Perspective: Mechanisms Of Proteinreceptor Bindingmentioning
confidence: 99%
“…Phosphotriesterase, 31 thrombin, 32 and glucose/galactose binding protein (GGBP) 19 all have two or three identifiable structures in equilibrium. Their ligand-binding mechanism has been described as CS because the ligands shift the majority of the population into the native state.…”
Section: A Historical Perspective: Mechanisms Of Proteinreceptor Bindingmentioning
confidence: 99%